Grupa nominalna w ustawach. System wewnątrztekstowych-odniesień - Łapa, Romana (Slavia Occidentalis, 2016)
This paper deals with a group of contemporary legal texts which have the form of statutes. The author describes the anaphoric relation between nominal groups (NG) constituted by an event-driven element and sentences which are linearly prior to these groups, the so-called antecedents. The analysis, founded on principles of syntax with a semantic basis, provides observations about restrictions in the formalisation of elements of the semantic base whose elements can be connected with the use of NG. The disclosure of elements of the content plan, excluding exceptions, entails a condensation which causes that categorical meanings that are the most intensely governed and communicatively relevant are fulfilled on the surface. The inability to reproduce the meaning of the “grammatical agent” causes that NG with a constitutive event-driven element are an indication of the depersonalisation attributed to legal texts. The repeatability of NG, mainly one- and two-component phrases, as well as their initial location in an utterance are factors depicting another feature of statutes: syntactic schematism. The author also demonstrates that the system of intratextual references is not the same in various variants of the Polish language. In the statute, as a genre of the legal language, its specific nature is already noticeable within one of the systematising units of the legal text, i.e. the article. The specific nature of the examined relation is conditioned by (1) the proper arrangement of structures connected with a network of references, and (2) the manner of their denotation. These features are the results of adherence to the editorial principles of legal texts.